Behavioural intention for fraudulent reporting behaviour using cognitive theory - Mohd Zawawi, Siti Noor Hayati; Jusoff, Kamaruzaman; Abdul Rahman, Rashidah; Muhd Idris, Kamil (Canadian Center of Science and Education, 2008)
Fraudulent financial reporting is a serious social problem that has spread worldwide. The consequences of it can be detrimental to many stakeholders. Thus, fraudulent financial reporting has to be prevented and combated. Fraudulent financial reporting involves human deviant behaviour. Thus, to prevent it from occurring, the root causes that relate to deviant human behaviour have to be identified. This paper tries to explain how the social behavioural theory, in particular the theory of reasoned action can be used to explain for fraudulent financial reporting behaviour.